An Exposition Into the Computation of the Last Letters of the 83rd Ayats of Suratul Yasiin in the Qur’an Kareem - Umaru Ibrahim Ladan; Huud Shittu; Ibrahim, Abdullahi Muhammad (Ibzar); Muhammad Munir Ilyas (Penerbit Hellow Pustaka, 2026)
This article obtained a computational analysis of the last letters of the 83rd ayats of the 36th Surah (Suratul Yasiin) of the Holy Qur’an Kareem. The proofs were achieved by deft deployment of even properties, odd properties and basic arithmetic operations. The analysis computes the exact number (114) of Surahs in the Holy Qur’an. The result shows conclusively the difference of the number of the last letter of the first ayat and the sum of difference of the even number and odd number of the ayats ending with “Mimun” and “Nunun” in the 36th Surah (Suratul Yasiin) is equal to the number (114) of Surah in the Holy Qur’an Hakiim.